Removing Self-stigma: The Successes of People with Schizophrenia in Removing Self-stigma Through Self-control - Franciscus Adi Prasetyo; Jajang Gunawijaya (Laboratory of General Psychology, Faculty of Psychology, Universitas Surabaya, 2018)
Self-stigma experienced by people who experience schizophrenia has influence on reduced self-esteem, on powerlessness, the weakening of hope, and a motivation towards recovery. The aim of this study is to explain the efforts of people suffering schizophrenia to manage their self-stigma through self-control, using a case study approach. Based on the purposive sampling technique, five people with schizophrenia were selected as the cases to be studied. Data collection techniques utilized in-depth interviews, observation, and documentary studies. The analysis of the study data employed the stages of data reduction, data display, and data verification. Improvement in study quality employed the triangulation of data sources by checking the data to determine its consistency. The results of this study indicate that people with schizophrenia who have the ability to self-control can overcome self-stigma through changes in the manner of viewing themselves, self-training through activities, having endurance, having an honest approach, being able to explain schizophrenia from a positive viewpoint, having initiative, and having a positive attitude and the courage to face challenges.